Avaliação da impulsividade em ratos privados de sono REM - Pezzato, Fernanda A.; Silveira, Drielly T. L. [UNESP]; Novais, Diego B. [UNESP]; Hoshino, Katsumasa [UNESP] (My University, 2012)
The progress of knowledge in the area of mental health still depends, at least in part, on the development of experimental paradigms using laboratory animals. In such context, sleep deprivation and its effects were proposed as an animal model of mania. Although being a prominent manifestation of mania, the increased impulsivity in sleep deprived rats seems to be not experimentally confirmed, albeit its occurrence foresaw. Such fact may be explained as due the short lasting duration of the behavioral effects of sleep deprivation, which seems to hinder long lasting evaluations. The present study, therefore, demonstrated an alternative way to operationally apprehend impulsivity and used it to confirm the higher impulsivity levels in sleep deprived rats. The latency, number of episodes, and the total time displayed by rats to move from a safe platform to narrow runways, where the risk to drop into a water tank was high, showed to lower after experiencing fall, indicating an increase in consequence evaluation. Sleep deprived rats showed a significantly greater number of displacements to strait runways and a greater time spent in this risk situation. It is concluded that the method used is reliable and allows confirming the occurrence of enhanced impulsivity in sleep deprived rats.
Assessment of impulsivity in REM-sleep deprived rats
Keywords: Animal model; Behavioral methods; Impulsivity; Mania; Sleep deprivation